Skyrmion Formation in Nanodisks Using Magnetic Force Microscopy Tip - Mateusz Zelent; Iuliia V. Vetrova; Jan Šoltýs; Xiaoguang Li; Yan Zhou; Vladislav A. Gubanov; Alexandr V. Sadovnikov; Tomas Šcepka; Jan Dérer; Roman Stoklas; Vladimír Cambel; Michal Mruczkiewicz (Nanomaterials, 2021)
We demonstrated numerically the skyrmion formation in ultrathin nanodisks using a magnetic force microscopy tip. We found that the local magnetic field generated by the magnetic tip significantly affects the magnetization state of the nanodisks and leads to the formation of skyrmions. Experimentally, we confirmed the influence of the local field on the magnetization states of the disks. Micromagnetic simulations explain the evolution of the magnetic state during magnetic force microscopy scanning and confirm the possibility of skyrmion formation. The formation of the horseshoe magnetic domain is a key transition from random labyrinth domain states into the skyrmion state. We showed that the formation of skyrmions by the magnetic probe is a reliable and repetitive procedure. Our findings provide a simple solution for skyrmion formation in nanodisks.